Krytyka Goffmanowskiej koncepcji statku morskiego jako instytucji zamkniętej - Janiszewski, Ludwik (Wydział Prawa i Administracji UAM, 1987)
Most sociologists researching a ship, especially those analizing the social structure of people who work and live there and the system of managing and commanding a ship, refer to the conception of „the total institution" formulated by a distinguished American scholar Ervin Goffman. The essence of his conception consists in isolating and analysing four main features (attributes) which are to distinguish a total institution; including a ship, from other social institutions. The present article contains criticism and formulates doubts with respect to the scientific status of Goffman's conception and its application as a theoretical model in empirical studies of a ship.
The Criticism of Goffman's Conception of Ship as the Closed Institution